1995
DOI: 10.1093/nar/23.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific methylation and expression of an imprinted U2afl-rsl (SP2) gene

Abstract: The mouse U2af1-rs1(SP2) gene, which was cloned by a two-dimensional genome scanning method, is expressed exclusively from the paternally inherited chromosome. This gene has significant similarity to U2AF and located in chromosome 11, of which maternal duplication/paternal deficiency results in a small body. In this report, we cloned genomic U2af1-rs1(SP2) and found its promoter was methylated in a maternal-allele-specific manner. This allelic methylation was not established in parental gametes, but establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
37
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 18 publications
5
37
0
Order By: Relevance
“…Of the AS transcripts described, the b transcript is most likely to be functionally significant because it is associated with recognizable promoter elements and contains four exons. In addition, all of the AS transcripts are transcribed through the tandem repeat and we cannot exclude a structural function for the repeat at the RNA level, particularly as certain transcripts of the mouse imprinted Ipw, U2af, and Xist genes also contain tandem repeats (9,23,24). At present, we do not know whether the P0 and P1 sense transcripts and the overlapping AS transcripts are coexpressed within individual cells, or whether there exists cellular mosaicism with respect to their expression.…”
Section: Discussionmentioning
confidence: 93%
“…Of the AS transcripts described, the b transcript is most likely to be functionally significant because it is associated with recognizable promoter elements and contains four exons. In addition, all of the AS transcripts are transcribed through the tandem repeat and we cannot exclude a structural function for the repeat at the RNA level, particularly as certain transcripts of the mouse imprinted Ipw, U2af, and Xist genes also contain tandem repeats (9,23,24). At present, we do not know whether the P0 and P1 sense transcripts and the overlapping AS transcripts are coexpressed within individual cells, or whether there exists cellular mosaicism with respect to their expression.…”
Section: Discussionmentioning
confidence: 93%
“…At pres ent, the nature of the primary im print and the molecu lar basis by which genes are recognized as paternally or maternally derived are still unknown. First evidence that méthylation plays an important role in genomic im printing came from the observation that many transgenes become hypomethylated after passage through the male germline and hypermethylated after passage through the female germline (Surani et a l,, 1988), Analysis of four imprinted genes in the mouse, H19 (Bartolomei et al, 1993;Ferguson-Smith et a l, 1993;Brandeis et al, 1993;Feil et al, 1994), insulinlike growth factor II {Igf2) (Sasaki et a l, 1992;Bran deis et al, 1993;Feil et al, 1994), Igf2 receptor (Igf2r) (Stôger et a lv 1993), and U2afl-rsl (SP2) (Hatada et al, 1995), has revealed that regions within the gene or adjacent to it are methylated in a parent-specific manner, The mouse Igf2r gene is expressed exclusively from the maternally inherited chromosome in fetal and adult tissues (Barlow et al, 1991), with the exception of the head and the brain, where biallelic expression has been observed (Villar and Pedersen, 1994). During preimplantation development, both maternal and pa ternal Ig f2 r alleles are expressed (Latham et al, 1994;Szabô and Mann, 1995), indicating that silencing of the paternal allele is a secondary event.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the actual status of allele-specific expression of imprinted genes during early development, it appears that some imprinted genes do exhibit parentalspecific expression during early development, whereas others may not (Rappolee et al 1992;Latham et al 1994Latham et al , 1995Hatada et al 1995;Tremblay et al 1995). These studies, however, present one or more of the following difficulties: {1) Total expression levels are unknown or uncertain (It is possible that allele-specific modes of expression may vary according to expression level); (2) parental-specific expression examined in gynogenetic and androgenetic ova may not be representative of that in normal ova [interaction between the maternal and paternal genomes may be required for the normal establishment of monoallelic expression {Latham et al 1994}1;…”
mentioning
confidence: 99%